The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.4081/monaldi.2020.1399
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous pneumomediastinum in COVID-19 pneumonia

Abstract: Spontaneous pneumomediastinum is a benign entity but can worsen the underlying condition with which it is associated. We evaluated the incidence and the clinical relevance of spontaneous pneumomediastinum in a consecutive series of 102 patients with COVID-19 pneumonia. Six cases of pneumomediastinum were identified by high-resolution chest CT-scan. Three patients required early intubation, and one of them died, while in in the remaining subjects the clinical course was benign. The presence of pneumomediastinum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 6 publications
1
26
0
3
Order By: Relevance
“…There are isolated reports of PNX/PMD as a complication of COVID-19 ARDS. 13 , 14 , 15 , 16 , 17 However, currently, there are few published data on the incidence and outcome of these complications in this specific patient population. 18 Furthermore, early predictors of PNX/PMD remain poorly described.…”
mentioning
confidence: 99%
“…There are isolated reports of PNX/PMD as a complication of COVID-19 ARDS. 13 , 14 , 15 , 16 , 17 However, currently, there are few published data on the incidence and outcome of these complications in this specific patient population. 18 Furthermore, early predictors of PNX/PMD remain poorly described.…”
mentioning
confidence: 99%
“…The presence of spontaneous pneumomediastinum in COVID-19 was associated with severe clinical course requiring aggressive management in a retrospective analysis by Loffi et al in a tertiary care center in Northern Italy which was the first European area to be hit by COVID-19 [ 24 ]. Wang et al performed a retrospective analysis of 248 COVID-19 patients and found the incidence of pneumothorax to be 24% in those with mechanical ventilation, the overall incidence was 2.01% and incidence in patients with ARDS was 10%.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of SP in non-ventilated patients remains unknown. However, the Macklin effect has been proposed as a possible etiology [3] owing to the SARS-CoV-2 propensity to damage type 2 pneumocytes [4]. The Macklin effect starts with alveolar rupture secondary to direct alveolar injury, leading to air leaking and dissection along the bronchovascular sheaths and eventually spreading of air within the mediastinum [5].…”
Section: Discussionmentioning
confidence: 99%
“…Due to unreliable sensitivity of reverse transcriptase polymerase chain reaction (RT-PCR), chest X-ray (CXR) and high-resolution computed tomography (HRCT) chest are often used to support a diagnosis and gauge severity in COVID-19 infection [2]. HRCT can show parenchymal changes ranging from ground-glass opacities to widespread consolidation [3]. Seldom have some extra-parenchymal findings such as pneumomediastinum been reported.…”
Section: Introductionmentioning
confidence: 99%